Corn silk polysaccharides attenuate diabetic nephropathy through restoration of the gut microbial ecosystem and metabolic homeostasis - Dong, Wenting; Zhao, Yuanyuan; Li, Xiuwei; Huo, Jinhai; Wang, Weiming (Frontiers in Endocrinology, 2023)
Introduction The pathogenesis of diabetic nephropathy (DN) is complex, inflammation is the central link among the inducing factors in the existing research, and the gutkidney axis could scientifically explain the reasons for the accumulation of chronic low-grade inflammation. As both a medicine and food, corn silk contains abundant polysaccharides. Historical studies and modern research have both confirmed its intervention effect on diabetes and DN, but the mechanism of action is unclear. Methods In this study, a DN rat model was generated, and the therapeutic effect of corn silk polysaccharides (CSPs) was evaluated based on behavioral, histopathological and biochemical indicators. We attempted to fully understand the interactions between CSPs, the gut microbiota and the host at the systemic level from a gut microbiota metabolomics perspective to fundamentally elucidate the mechanisms of action that can be used to intervene in DN. Results Research has found that the metabolic pathways with a strong correlation with CSPs were initially identified as glycerophosphate, fatty acid, bile acid, tyrosine, tryptophan and phenylalanine metabolism and involved Firmicutes, Bacteroides, Lachnospiraceae-NK4A136- group and Dubosiella, suggesting that the effect of CSPs on improving DN is related to changes in metabolite profiles and gut microbiota characteristics. Discussion CSPs could be harnessed to treat the abnormal metabolism of endogenous substances such as bile acids and uremic toxins caused by changes in gut microbiota, thus alleviating kidney damage caused by inflammation. In view of its natural abundance, corn silk is safe and nontoxic and can be used for the prevention and treatment of diabetes and DN.